THE CLINICAL AND LABORATORY DIAGNOSTICS OF INFLAMMATION CAUSED BY INFECTIVE ENDOCARDITIS - N. A. Semenenko (Сеченовский вестник)
This paper describes a comprehensive study of and approaches to the diagnosis of the different phases of disease and inflammation caused by infectious endocarditis.